TRANSITION OF CARBON IMPURITY IN CRYSTAL SILICON OF SEMICONDUCTOR PURITY - Kritskaya , Tatiana; Shvartsman , Leonid; Kiselev , George (Scientific Journal "Metallurgy", 2020)
The carbon concentration in silicon of semiconductor purity may be at a level exceeding the content of other background impurities. Its presence significantly affects the processes of defect-impurity interaction during monocrystals growth and heat treatment, the device structures dynamic characteristics, as well as the formation of defective complexes in silicon when exposed to external factors (temperature, radiation, etc.). The behavior and sources analysis of the carbon impurity in semiconductor purity silicon obtained by carbothermal quartzite reduction, and at the stages of the Siemens process is completed. It was found that the electrolysis chlorine used in the synthesis of hydrogen chloride contains carbon-containing compounds: chloromethane, chloroethane, dichloromethane, carbon tetrachloride and others. Calculation and experimental studies based on long-term observations of the technological processes progress at existing industrial enterprises have been carried out. It was shown that when calculating distillation columns, one should focus on the separation coefficient of limiting impurities for volatile combinations. The transition coefficients and the forms of the presence of carbon and other impurities in the main and intermediate products of technological processes are determined. The role of carbon in the polycrystalline semiconductor purity silicon further stages of processing and using is analyzed. The level of impurities in raw materials (quartzites, reducing agents) is estimated, the material products balance involved in the synthesis of trichlorosilane is carried out, the principle for calculating distillation columns is described. The choice is justified and effective methods of carbon removal at the stages of the technology main stages for producing semiconductor silicon are presented. The level of maintenance of admixtures is appraised in raw material materials (quartzites, repairers), material balance of products, participating in the process of synthesis of trichlorosilane is conducted, principle of calculation of fractionators is expounded and the choice of effective methods of cleaning is reasonable.